Potential and Problems of SCO Expansion - D. Xiaoxing (Международная аналитика)
The paper provides analysis of pros and contras of SCO expansion in future. The international influence of the organization will be accompanied at the same time by new political and organizational problems, one of the main being the coordination of decisions on the basis of consensus.